Unsur Fisik dan Batin pada Puisi ”Meditasi 1”, ”Meditasi 2”, ”Meditasi Waktu”, dan ”Meditasi Hujan” Karya Heri Isnaini - Nisa Fitria; Risa Anggraeni; Melysa Kurnia Sari (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
Several titles of poems related to meditation by Heri Isnaini are exciting works to study, especially on the physical and inner elements of the poem. The inner elements are interrelated with the intrinsic elements contained in the poem, such as theme, feeling, tone, atmosphere, and the message to be conveyed. In contrast, the physical elements refer to the visual and auditory aspects of the poem, such as word choice, imagery, language style, typography, concrete language, and rhyme. This paper uses the literature study research method, namely by collecting data by reviewing books, as well as various reports related to the problem to be solved. This research aims to describe and examine the physical and mental elements, as well as understand the relationship between the two elements in building overall meaning in the poems “Meditation 1”, “Meditation 2”, “Time Meditation”, and “Rain Meditation” by Heri Isnaini. The results of this study show that the physical and mental elements in poetry have a complementary relationship in expressing a deep message, thus producing a complete meaning and touching emotionally and intellectually.